2001
DOI: 10.4049/jimmunol.166.7.4678
|View full text |Cite
|
Sign up to set email alerts
|

Two Proteins Modulating Transendothelial Migration of Leukocytes Recognize Novel Carboxylated Glycans on Endothelial Cells

Abstract: We recently showed that a class of novel carboxylated N-glycans was constitutively expressed on endothelial cells. Activated, but not resting, neutrophils expressed binding sites for the novel glycans. We also showed that a mAb against these novel glycans (mAbGB3.1) inhibited leukocyte extravasation in a murine model of peritoneal inflammation. To identify molecules that mediated these interactions, we isolated binding proteins from bovine lung by their differential affinity for carboxylated or neutralized gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 48 publications
3
163
0
Order By: Relevance
“…Recently, different compounds that also participate in the formation of extracellular matrix of connective tissue or basement lamina were found to associate with S100 proteins. For neutrophils, involvement of S100A8 and S100A9 in the modulation of transendothelial migration by interaction with glycosaminoglycans and carboxylated glycans has been shown (40,41). In addition, S100A8 and S100A9 have been described to increase adhesion of monocytes to fibronectin (42).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, different compounds that also participate in the formation of extracellular matrix of connective tissue or basement lamina were found to associate with S100 proteins. For neutrophils, involvement of S100A8 and S100A9 in the modulation of transendothelial migration by interaction with glycosaminoglycans and carboxylated glycans has been shown (40,41). In addition, S100A8 and S100A9 have been described to increase adhesion of monocytes to fibronectin (42).…”
Section: Resultsmentioning
confidence: 99%
“…S100A8 and S100A9, induced in MEC by IL-1␤ and TNF in vitro (26), are observed in neovessels, but not larger vessels, in inflammatory lesions (15). The complex is deposited on the endothelium by transmigrating leukocytes; S100A9 binds endothelial cells (EC) via heparan sulfate proteoglycans (58) and to carboxylated N-glycans on activated EC (59). S100A8 has functions separate from those involving heterodimerization with S100A9 (60), and although we have not confirmed S100A8-SNO in EC, it may modulate microvascular function in inflamed vessels.…”
Section: Discussionmentioning
confidence: 99%
“…70) It was reported that calprotectin interacts with carboxylated glycan 71) or sulfated glycosamininoglycans 72) on endothelial cells. It was also proposed that a 2 -macroglobulin is a ligand on endothelial cells for calprotectin.…”
Section: Fig 2 Effect Of Calprotectin On the Growth Of Various Tumomentioning
confidence: 99%